FACTORS INFLUENCING AUDITORS' ACCEPTANCE OF THE PRACTICE REVIEW SYSTEM - Sarina Ismail,; Hasnah Haron,; Ishak Ismail,; Gerald Vinten, (Asian Academy of Management Journal, 2007)
This research was carried out to identify the factors that influence auditors' acceptance of the Practice Review System. Using a theoretical model based on the Decomposed Theory of Planned Behavior, this study aims to identify the factors influencing acceptance of the Practice Review System. Questionnaire survey was used in research. Systematic random sampling was adopted with 1,000 sets of questionnaire distributed and 123 completed questionnaire returned for analysis. The results indicated that the proposed model explained 64.6% of the variance in intention to accept the Practice Review System. The results from this study highlight that salient beliefs including perceived usefulness and rule observation behavior are highly relevant in assessing attitude towards acceptance of Practice Review System, while attitude is strongly associated with intention. The implications of this study are beneficial for practitioners in identifying the factors influencing auditors' acceptance of the Practice Review System. Hence, this would enable them to better develop implementation strategies for acceptance of the Practice Review System.